ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA PADA MATERI RELASI DAN FUNGSI KELAS VIII DI SMPN 1 TANJUNGANOM - Anggraini, Ninda Sundari; Hamidah, Dewi; Rahayu, Dwi Shinta (Jurnal Pendidikan Matematika (JUPITEK), 2021)
This study aims to determine the students' higher order thinking skills (HOTS) in subject of relation and function. This type of research is a qualitative research with the research subjects being class VIII-1 of SMPN 1 Tanjunganom in the academic year 2020/2021 with a total of 32 students. The data obtained from the HOTS test and interviews. Analysis data used in the form of Bloom's taxonomy analysis. From the results of research conducted by researchers, it shows that the taxonomic percentages of blooms based on each level of C4 (analyze), C5 (evaluate), and C6 (create) are 61.98%, 47.17%, and 48.96%. From the results of the study, the students' HOTS abilities were 1 student in the very good category, 6 students in the good category, 22 students in the sufficient category, 3 students in the poor category, and no students in the very poor category